Communicating About Risk in a Food-Obsessed World—Reprised. Issue 2 (March 2019) - Rowe, Sylvia; Alexander, Nick
Abstract : Nutrition and health communicators have, in the past, struggled with messaging around dietary guidance, weight management, and obesity. In recent months, a plethora of food safety crises has focused the attention of communicators on how best to deal with messages under conditions of crisis and high risk. Numerous cases of Salmonella, cyclosporiasis, Listeria, a deadly form of Escherichia coli, and other pathogenic outbreaks have raised consumers' concern about the safety of the food they consume as well as about the US food system itself. In this article, the authors revisit well-established rules for communicating about scientific uncertainty and real or perceived health risks around food. They analyze some of the more serious communication challenges in the most recent romaine lettuce and other food safety scares, and they propose reasons for the ensuing public confusion. Finally, they offer suggestions on meeting the evolving challenges in the new digital information era, with its perpetual news deadlines.